2023
DOI: 10.1111/acel.13764
|View full text |Cite
|
Sign up to set email alerts
|

Reversine ameliorates hallmarks of cellular senescence in human skeletal myoblasts via reactivation of autophagy

Abstract: Cellular senescence leads to the depletion of myogenic progenitors and decreased regenerative capacity. We show that the small molecule 2,6‐disubstituted purine, reversine, can improve some well‐known hallmarks of cellular aging in senescent myoblast cells. Reversine reactivated autophagy and insulin signaling pathway via upregulation of Adenosine Monophosphate‐activated protein kinase (AMPK) and Akt2, restoring insulin sensitivity and glucose uptake in senescent cells. Reversine also restored the loss of conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…However, their precise role during AD progression is unknown. Reversine has been proposed as a therapeutic option against cellular senescence [ 58 ]. This compound increases the differentiation potential of progenitor cells toward the neuroectodermal lineage [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, their precise role during AD progression is unknown. Reversine has been proposed as a therapeutic option against cellular senescence [ 58 ]. This compound increases the differentiation potential of progenitor cells toward the neuroectodermal lineage [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…This compound increases differentiation potential of progenitor cells toward the neuroectodermal lineage (56). Interestingly, it has been demonstrated that Reversine is able to reactivate insulin pathway, autophagy, glucose uptake and restore glycolytic-Krebs cycle connectivity, rewiring mitochondrial functionality in senescent cells (55). All these processes are considered hallmarks of a neurodegenerative process (57) suggesting Reversine as a potential therapeutic component in AD.…”
Section: Discussionmentioning
confidence: 99%
“…This problem may be addressed by improving host cell attachment to the culture vessel using various methods ( Madden et al, 2015 ; Bettadapur et al, 2016 ; Denes et al, 2019 ; Martins et al, 2022 ). Finally, cellular senescence may also pose a limit on the maximal passages of KD3 cells and may be ameliorated by reversine treatment ( Rajabian et al, 2023 ). Mild heat stress from temperature fluctuations of cell culture incubators may also induce differentiation and needs to be avoided ( Yamaguchi et al, 2010 ).…”
Section: General Notes and Troubleshootingmentioning
confidence: 99%